Nonlinear dynamic analysis of gear-rotor-bearing system equipped with HSFD under hydraulic actuator active control. Issue 1 (March 2021) - Jian, Bo-Lin; Chu, Li-Ming; Chang, Yuh-Ping; Chang-Jian, Cai-Wan
In this study, the nonlinear dynamic analysis of the hybrid squeeze film damper mounted on a gear-rotor-bearing system is presented. The strong nonlinear oil film force, nonlinear rub-impact force between the rotor and stator, and the gear meshing force are considered in this study. The bifurcation diagrams are plotted using a dimensionless imbalance factor, damping coefficient, and speed ratio as control parameters in this study. The beginning of chaotic motion is identified by phase diagrams, power spectrum, Poincaré maps, bifurcation diagrams, maximum Lyapunov exponent, and the fractal dimension of the system. The numerical results provide useful insights into the design and development of a gear-rotor-bearing system for rotating machinery that operates at high speeds and highly nonlinear conditions. Hybrid squeeze film damper is used to suppress irregular dynamic behaviors and reduce greater amplitude, even if the rotational speed of the rotating machine is higher, which is also confirmed in this study.